1985
DOI: 10.1111/j.1365-2125.1985.tb05044.x
|View full text |Cite
|
Sign up to set email alerts
|

Antisecretory effect and oral pharmacokinetics following low dose omeprazole in man.

Abstract: The effects of single and repeated doses of omeprazole 10 mg on gastric secretion were studied in a group of six healthy subjects. Single doses had no significant effect on basal or stimulated acid output. After 7 days of treatment, there was a 93.1% reduction in basal acid output (P < 0.02) and a 66.5% reduction in stimulated output (P < 0.01). Pepsin output was not affected. Systemic availability of omeprazole, as reflected in the AUC, increased significantly (P < 0.05) with repeated dosing. Low doses of ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…There was marked inter-individual variation in tmax, Cmax and AUC as was noted by Tuynman et al (1987) and by ourselves in previous studies (Howden et al, 1984(Howden et al, ,1985. In this study, we did not detect any significant alterations in tmax, Cmax or AUC for omeprazole when it was given with antacid or following metoclopramide.…”
supporting
confidence: 70%
“…There was marked inter-individual variation in tmax, Cmax and AUC as was noted by Tuynman et al (1987) and by ourselves in previous studies (Howden et al, 1984(Howden et al, ,1985. In this study, we did not detect any significant alterations in tmax, Cmax or AUC for omeprazole when it was given with antacid or following metoclopramide.…”
supporting
confidence: 70%
“… 11 Whilst the greater antisecretory effect of lansoprazole is not large enough to affect oesophagitis healing rates, it may accelerate symptom relief during the first few days of treatment. Omeprazole has relatively low bioavailability in the first few days of administration and may take up to 5 days to achieve a pharmacodynamic steady state 17 –20 . It then exerts enough antisecretory effect to maintain intragastric pH above 4 for a sufficient period of time to heal oesophageal erosions, just as effectively as lansoprazole 2 …”
Section: Discussionmentioning
confidence: 99%
“…13,43,44 Peak plasma concentrations and AUe increase significantly after five to seven days of treatment. Howden et al demonstrated mean increases in the AUe of 86 and 128 percent after seven days ofrepeated oral doses of 30 and 60 mg/d, respectively.…”
Section: Bsoryflonmentioning
confidence: 97%